High-refractive-index large-particle-size glass beads for road marking and spheroidizing forming preparation method thereof
By adopting high-refractive index large-particle glass microbeads and their spheroidization preparation methods, the problem of insufficient visibility of traditional road markings in night or inclement weather conditions is solved, and the effect of significantly improving the visibility of the signs is achieved, and road safety and energy efficiency are improved.
Patent Information
- Application Number
- CN202411825986.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The traditional painted signs of existing road markings are insufficiently visible at night or in severe weather conditions, making it difficult for drivers to identify signs in time and increase the risk of traffic accidents.
High-refractive index large-particle glass beads and their spheroidization preparation method are adopted to form glass beads with high refractive index by mixing and melting the composites of titanium dioxide, silica, barium nitrate, zirconium nitrate, zinc oxide, boric acid, calcium fluoride, Nb2O5 and La2O3-ZrO2 in a specific proportion. The method includes steps such as water quenching, drying, ball milling and screening, and finally obtains glass beads with high refractive index by spray forming.
It significantly improves the visibility of the signs, and even at high speeds, it can provide the driver with sufficient reaction time, thereby effectively reducing the occurrence of traffic accidents. At the same time, the reflective properties of high-refractive index glass beads can provide effective indications and warnings without the need for external power, improving safety and reducing energy consumption.
Abstract
Description
Technical Field
[0001] The invention relates to glass microbeads, in particular to high-refractive-index and large-diameter glass microbeads for road markings and a spheroidizing and molding preparation method thereof. Background Art
[0002] Glass beads are classified according to their refractive index and are usually divided into three main grades. The first is low-refractive-index glass beads with a refractive index below 1.7. These beads are usually not the first choice in optical applications because they have weak refractive power. The second is quasi-high-refractive-index glass beads with a refractive index between 1.7 and 1.9. Their refractive power is improved compared to the former, but may still not be enough to meet the requirements in some high-end applications. Finally, there are high-refractive-index glass beads with a refractive index above 1.9. These beads have become a hot spot for research and application due to their excellent optical properties, especially in the manufacture of retroreflective materials, where they exhibit unparalleled retroreflective capabilities.
[0003] High-refractive-index glass microbeads play a vital role in the production of retroreflective materials, a special composite film material that combines the principles of optical refraction and reflection to achieve efficient light reflection. In countries where glass industry technology is relatively mature, this material has been widely researched, developed and applied. It is not only used in traffic signs and signal signs, but also under the illumination of vehicle headlights, these signs can be clearly identified even at a distance of 500 to 700 meters. The reflective ability of this material is particularly prominent at night or in bad weather conditions. Its reflective intensity is nearly 100 times that of traditional paint signs, which makes it have great potential in improving road safety.
[0004] When driving at night, the maximum visibility distance of traditional paint signs under the illumination of car lights is usually only 50 to 100 meters, which is far from enough when driving at high speeds. When the speed exceeds 100 kilometers per hour, the driver's reaction time is greatly shortened. If the visibility of traffic signs is insufficient, it is easy for the driver to fail to recognize the signs in time, thus causing traffic accidents. However, retroreflective materials made of high-refractive glass beads can significantly improve the visibility of signs, and even when driving at high speeds, they can provide drivers with sufficient reaction time, thereby effectively reducing the occurrence of traffic accidents.
[0005] With the continuous advancement of technology and the continuous expansion of application fields, the application of high refractive index glass beads is no longer limited to the field of road traffic. They are also widely used in other occasions that require high visibility and safety, such as mining, fire fighting, emergency rescue, sanitation, municipal administration and construction industries. The reflective properties of this material enable it to provide effective instructions and warnings without the need for external power, which not only improves safety but also reduces energy consumption, meeting the requirements of modern society for energy conservation and environmental protection. Therefore, high refractive index glass beads and retroreflective materials made of them have broad prospects and important application value in future development. Summary of the invention
[0006] The present invention aims to provide a high-refractive-index and large-diameter glass microsphere for road marking and a spheroidization molding preparation method thereof.
[0007] The present invention is achieved through the following technical solutions:
[0008] A high-refractive-index large-particle glass microbead for road marking comprises, by weight: 30-40 parts of titanium dioxide, 30-40 parts of silicon dioxide, 10-15 parts of barium nitrate, 10-15 parts of zirconium nitrate, 5-7 parts of zinc oxide, 3-5 parts of boric acid, 3-5 parts of calcium fluoride, 5-110 parts of Nb2O5, and 5-15 parts of La2O3-ZrO2 compound.
[0009] Furthermore, the titanium dioxide is 30 parts, the silicon dioxide is 30 parts, the barium nitrate is 10 parts, the zirconium nitrate is 10 parts, the zinc oxide is 5 parts, the boric acid is 1 part, the calcium fluoride is 3 parts, the Nb2O5 is 5-10 parts, and the La2O3-ZrO2 complex is 5-15 parts.
[0010] Furthermore, the titanium dioxide is 30 parts, the silicon dioxide is 30 parts, the barium nitrate is 10 parts, the zirconium nitrate is 10 parts, the zinc oxide is 5 parts, the boric acid is 1 part, the calcium fluoride is 3 parts, the Nb2O5 is 5 parts, and the La2O3-ZrO2 complex is 5 to 15 parts.
[0011] Furthermore, the titanium dioxide is 30 parts, the silicon dioxide is 30 parts, the barium nitrate is 10 parts, the zirconium nitrate is 10 parts, the zinc oxide is 5 parts, the boric acid is 1 part, the calcium fluoride is 3 parts, the Nb2O5 is 510 parts, and the La2O3-ZrO2 complex is 5 to 15 parts.
[0012] Furthermore, the preparation method of the La2O3-ZrO2 composite is:
[0013] ZrOCl2·8H2O and La(NO3)3·6H2O were dissolved in deionized water, and then 30 mL of anhydrous ethanol was added;
[0014] Ultrasonication for 1 h, then adjusting the pH with NH4OH, followed by vigorous stirring for 30 min;
[0015] Transfer to a high pressure reactor and react at 200°C for 20h;
[0016] Then it was cooled naturally to room temperature and then centrifuged to obtain a precipitate, which was washed with deionized water and then dried at 70 °C for 12 h and then calcined.
[0017] Furthermore, the molar ratio of ZrOCl2·8H2O to La(NO3)3·6H2O is 4.5:1, and the pH is adjusted to 10 with NH4OH. The calcination condition is calcination at 900°C for 12h.
[0018] The present invention also provides a spheroidization molding preparation method, characterized in that it includes the following steps: titanium dioxide, silicon dioxide, barium nitrate, zirconium nitrate, zinc oxide, boric acid, calcium fluoride, Nb2O5 and La2O3-ZrO2 are mixed evenly, then melted at 1200°C, the molten product is water quenched, ball milled after drying, and sieved to obtain a 50μm precursor. The precursor is divided into two paths, and the precursor in each path is mixed with fuel gas and oxidant under the impetus of compressed air, and sprayed into the combustion chamber through a nozzle;
[0019] The heating temperature in the combustion chamber is set to 1300°C, and the jet velocity of the nozzle is 75 m / s; the jet trajectories of the two nozzles intersect at one point;
[0020] The two jet paths share an intersection point, so that the molten glass bead precursor converges at this point; glass micro beads with high refractive index are obtained through the screening process. The angle at which the jet trajectories of the two nozzles intersect at one point is 75°.
[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0022] Calcination at 900°C for 12 hours helps improve the thermal stability and mechanical strength of the glass beads, allowing them to be used for a long time in harsh outdoor environments without being easily damaged. At a high temperature of 1300°C and a spray speed of 75 m / s, the precise intersection of the two nozzles in the combustion chamber ensures precise control of the melting and molding process of the glass beads, thereby obtaining high-quality high-refractive index glass beads. The addition of Nb2O5 and La2O3-ZrO2 composites not only improves the refractive index of the glass beads, but also maintains a high yield rate. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0024] The preparation method of the La2O3-ZrO2 complex in the present invention is as follows: weigh 45mmol ZrOCl2·8H2O and 10mmol La(NO3)3·6H2O, dissolve them in 10mL deionized water, and then add 30mL anhydrous ethanol; ultrasonicate for 1h, then adjust the pH to 10 with NH4OH, then stir vigorously for 30min, transfer to a high-pressure reactor, react at 200°C for 20h; then cool naturally to room temperature, then centrifuge to obtain a precipitate, wash the precipitate with deionized water for 5 times, then dry at 70°C for 12h, and then calcine at 900°C for 12h to obtain the La2O3-ZrO2 complex.
[0025] Example 1
[0026] A high-refractive-index large-particle glass microbead for road marking comprises, by weight: 30 parts of titanium dioxide, 30 parts of silicon dioxide, 10 parts of barium nitrate, 10 parts of zirconium nitrate, 5 parts of zinc oxide, 3 parts of boric acid, 3 parts of calcium fluoride, 5 parts of Nb2O5, and 5 parts of La2O3-ZrO2 compound.
[0027] A spheroidization preparation method for high-refractive index large-particle glass microspheres for road markings: titanium dioxide, silicon dioxide, barium nitrate, zirconium nitrate, zinc oxide, boric acid, calcium fluoride, Nb2O5 and La2O3-ZrO2 are mixed evenly, then melted at 1200°C, the molten product is water quenched, ball milled after drying, and sieved to obtain a 50μm precursor. The precursor is divided into two paths, and the precursor in each path is mixed with fuel gas and oxidant under the impetus of compressed air and injected into a combustion chamber through a nozzle. The heating temperature in the combustion chamber is set to 1300°C, and the injection speed of the nozzle is 75 m / s. In this process, the injection trajectories of the two nozzles intersect at one point, forming an angle of 75°. The two injection paths share an intersection point, so that the molten glass bead precursor converges at this point. Finally, high-refractive index glass microspheres are obtained through a screening process.
[0028] Example 2
[0029] A high-refractive-index large-particle glass microbead for road marking comprises, by weight, 30 parts of titanium dioxide, 30 parts of silicon dioxide, 10 parts of barium nitrate, 10 parts of zirconium nitrate, 5 parts of zinc oxide, 3 parts of boric acid, 3 parts of calcium fluoride, 5 parts of Nb2O5, and 10 parts of La2O3-ZrO2 compound.
[0030] A spheroidization preparation method for high-refractive index large-particle glass microspheres for road markings: titanium dioxide, silicon dioxide, barium nitrate, zirconium nitrate, zinc oxide, boric acid, calcium fluoride, Nb2O5 and La2O3-ZrO2 are mixed evenly, then melted at 1200°C, the molten product is water quenched, ball milled after drying, and sieved to obtain a 50μm precursor. The precursor is divided into two paths, and the precursor in each path is mixed with fuel gas and oxidant under the impetus of compressed air and injected into a combustion chamber through a nozzle. The heating temperature in the combustion chamber is set to 1300°C, and the injection speed of the nozzle is 75 m / s. In this process, the injection trajectories of the two nozzles intersect at one point, forming an angle of 75°. The two injection paths share an intersection point, so that the molten glass bead precursor converges at this point. Finally, high-refractive index glass microspheres are obtained through a screening process.
[0031] Example 3
[0032] A high-refractive-index large-particle glass microbead for road marking comprises, by weight, 30 parts of titanium dioxide, 30 parts of silicon dioxide, 10 parts of barium nitrate, 10 parts of zirconium nitrate, 5 parts of zinc oxide, 3 parts of boric acid, 3 parts of calcium fluoride, 5 parts of Nb2O5, and 15 parts of La2O3-ZrO2 compound.
[0033] A spheroidization preparation method for high-refractive index large-particle glass microspheres for road markings: titanium dioxide, silicon dioxide, barium nitrate, zirconium nitrate, zinc oxide, boric acid, calcium fluoride, Nb2O5 and La2O3-ZrO2 are mixed evenly, then melted at 1200°C, the molten product is water quenched, ball milled after drying, and sieved to obtain a 50μm precursor. The precursor is divided into two paths, and the precursor in each path is mixed with fuel gas and oxidant under the impetus of compressed air and injected into a combustion chamber through a nozzle. The heating temperature in the combustion chamber is set to 1300°C, and the injection speed of the nozzle is 75 m / s. In this process, the injection trajectories of the two nozzles intersect at one point, forming an angle of 75°. The two injection paths share an intersection point, so that the molten glass bead precursor converges at this point. Finally, high-refractive index glass microspheres are obtained through a screening process.
[0034] Example 4
[0035] A high-refractive-index large-particle glass microbead for road marking comprises, by weight: 30 parts of titanium dioxide, 30 parts of silicon dioxide, 10 parts of barium nitrate, 10 parts of zirconium nitrate, 5 parts of zinc oxide, 3 parts of boric acid, 3 parts of calcium fluoride, 10 parts of Nb2O5, and 5 parts of La2O3-ZrO2 compound.
[0036] A spheroidization preparation method for high-refractive index large-particle glass microspheres for road markings: titanium dioxide, silicon dioxide, barium nitrate, zirconium nitrate, zinc oxide, boric acid, calcium fluoride, Nb2O5 and La2O3-ZrO2 are mixed evenly, then melted at 1200°C, the molten product is water quenched, ball milled after drying, and sieved to obtain a 50μm precursor. The precursor is divided into two paths, and the precursor in each path is mixed with fuel gas and oxidant under the impetus of compressed air and injected into a combustion chamber through a nozzle. The heating temperature in the combustion chamber is set to 1300°C, and the injection speed of the nozzle is 75 m / s. In this process, the injection trajectories of the two nozzles intersect at one point, forming an angle of 75°. The two injection paths share an intersection point, so that the molten glass bead precursor converges at this point. Finally, high-refractive index glass microspheres are obtained through a screening process.
[0037] Example 5
[0038] A high-refractive-index large-particle glass microbead for road marking comprises, by weight: 30 parts of titanium dioxide, 30 parts of silicon dioxide, 10 parts of barium nitrate, 10 parts of zirconium nitrate, 5 parts of zinc oxide, 3 parts of boric acid, 3 parts of calcium fluoride, 10 parts of Nb2O5, and 10 parts of La2O3-ZrO2 compound.
[0039] A spheroidization preparation method for high-refractive index large-particle glass microspheres for road markings: titanium dioxide, silicon dioxide, barium nitrate, zirconium nitrate, zinc oxide, boric acid, calcium fluoride, Nb2O5 and La2O3-ZrO2 are mixed evenly, then melted at 1200°C, the molten product is water quenched, ball milled after drying, and sieved to obtain a 50μm precursor. The precursor is divided into two paths, and the precursor in each path is mixed with fuel gas and oxidant under the impetus of compressed air and injected into a combustion chamber through a nozzle. The heating temperature in the combustion chamber is set to 1300°C, and the injection speed of the nozzle is 75 m / s. In this process, the injection trajectories of the two nozzles intersect at one point, forming an angle of 75°. The two injection paths share an intersection point, so that the molten glass bead precursor converges at this point. Finally, high-refractive index glass microspheres are obtained through a screening process.
[0040] Example 6
[0041] A high-refractive-index large-particle glass microbead for road marking comprises, by weight, 30 parts of titanium dioxide, 30 parts of silicon dioxide, 10 parts of barium nitrate, 10 parts of zirconium nitrate, 5 parts of zinc oxide, 3 parts of boric acid, 3 parts of calcium fluoride, 10 parts of Nb2O5, and 15 parts of La2O3-ZrO2 compound.
[0042] A spheroidization preparation method for high-refractive index large-particle glass microspheres for road markings: titanium dioxide, silicon dioxide, barium nitrate, zirconium nitrate, zinc oxide, boric acid, calcium fluoride, Nb2O5 and La2O3-ZrO2 are mixed evenly, then melted at 1200°C, the molten product is water quenched, ball milled after drying, and sieved to obtain a 50μm precursor. The precursor is divided into two paths, and the precursor in each path is mixed with fuel gas and oxidant under the impetus of compressed air and injected into a combustion chamber through a nozzle. The heating temperature in the combustion chamber is set to 1300°C, and the injection speed of the nozzle is 75 m / s. In this process, the injection trajectories of the two nozzles intersect at one point, forming an angle of 75°. The two injection paths share an intersection point, so that the molten glass bead precursor converges at this point. Finally, high-refractive index glass microspheres are obtained through a screening process.
[0043] Comparative Example 1
[0044] A high-refractive-index large-particle glass microbead for road marking comprises, by weight, 30 parts of titanium dioxide, 30 parts of silicon dioxide, 10 parts of barium nitrate, 10 parts of zirconium nitrate, 5 parts of zinc oxide, 3 parts of boric acid, 3 parts of calcium fluoride and 5 parts of Nb2O5.
[0045] A spheroidization preparation method for high-refractive index large-particle glass microspheres for road markings: titanium dioxide, silicon dioxide, barium nitrate, zirconium nitrate, zinc oxide, boric acid, calcium fluoride and Nb2O5 are mixed evenly, then melted at 1200°C, the molten product is water quenched, ball milled after drying, and sieved to obtain a 50μm precursor. The precursor is divided into two paths, and the precursor in each path is mixed with fuel gas and oxidant under the impetus of compressed air and sprayed into a combustion chamber through a nozzle. The heating temperature in the combustion chamber is set to 1300°C, and the nozzle spray speed is 75 m / s. In this process, the spray trajectories of the two nozzles intersect at one point, forming an angle of 75°. The two spray paths share an intersection point, so that the molten glass bead precursor converges at this point. Finally, high-refractive index glass microspheres are obtained through a screening process.
[0046] Comparative Example 2
[0047] A high-refractive-index large-particle glass microbead for road marking comprises, by weight, 30 parts of titanium dioxide, 30 parts of silicon dioxide, 10 parts of barium nitrate, 10 parts of zirconium nitrate, 5 parts of zinc oxide, 3 parts of boric acid, 3 parts of calcium fluoride, 5 parts of Nb2O5, 2.5 parts of La2O3 and 2.5 parts of ZrO2.
[0048] A spheroidization preparation method for high-refractive index large-particle glass microspheres for road markings: titanium dioxide, silicon dioxide, barium nitrate, zirconium nitrate, zinc oxide, boric acid, calcium fluoride, Nb2O5, La2O3 and ZrO2 are mixed evenly, then melted at 1200°C, the molten product is water quenched, ball milled after drying, and sieved to obtain a 50μm precursor. The precursor is divided into two paths, and the precursor in each path is mixed with fuel gas and oxidant under the impetus of compressed air and injected into a combustion chamber through a nozzle. The heating temperature in the combustion chamber is set to 1300°C, and the injection speed of the nozzle is 75 m / s. In this process, the injection trajectories of the two nozzles intersect at one point, forming an angle of 75°. The two injection paths share an intersection point, so that the molten glass bead precursor converges at this point. Finally, high-refractive index glass microspheres are obtained through a screening process.
[0049] Test Example 1
[0050] The refractive indexes of Examples 1 to 6 and Comparative Examples 1 to 2 were measured by oil immersion method, and the yields of products with a size of 600 to 850 μm were sieved and counted, where the yields were the mass percentage of the sieved products to all products. See Table 1 for details.
[0051] Table 1 Test results
[0052] Refractive Index Yield rate (%) Example 1 2.02 91.4 Example 2 2.02 91.3 Example 3 2.04 92.7 Example 4 2.07 91.5 Example 5 2.07 90.6 Example 6 2.08 92.1 Comparative Example 1 2.01 60.7 Comparative Example 2 2.01 67.2
[0053] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high refractive index large particle size glass microsphere for road marking, characterized in that: The invention comprises, by weight: 30-40 parts of titanium dioxide, 30-40 parts of silicon dioxide, 10-15 parts of barium nitrate, 10-15 parts of zirconium nitrate, 5-7 parts of zinc oxide, 3-5 parts of boric acid, 3-5 parts of calcium fluoride, 5-110 parts of Nb2O5 and 5-15 parts of La2O3-ZrO2 compound.
2. The high refractive index large particle size glass microspheres for road marking according to claim 1, characterized in that: The titanium dioxide is 30 parts, the silicon dioxide is 30 parts, the barium nitrate is 10 parts, the zirconium nitrate is 10 parts, the zinc oxide is 5 parts, the boric acid is 1 part, the calcium fluoride is 3 parts, the Nb2O5 is 5-10 parts, and the La2O3-ZrO2 compound is 5-15 parts.
3. The high refractive index large particle size glass microspheres for road marking according to claim 2, characterized in that: The titanium dioxide is 30 parts, the silicon dioxide is 30 parts, the barium nitrate is 10 parts, the zirconium nitrate is 10 parts, the zinc oxide is 5 parts, the boric acid is 1 part, the calcium fluoride is 3 parts, the Nb2O5 is 5 parts, and the La2O3-ZrO2 compound is 5 to 15 parts.
4. The high refractive index large particle size glass microspheres for road marking according to claim 3, characterized in that: The titanium dioxide is 30 parts, the silicon dioxide is 30 parts, the barium nitrate is 10 parts, the zirconium nitrate is 10 parts, the zinc oxide is 5 parts, the boric acid is 1 part, the calcium fluoride is 3 parts, the Nb2O5 is 10 parts, and the La2O3-ZrO2 compound is 5 to 15 parts.
5. The high refractive index large particle size glass microspheres for road marking according to claim 1, characterized in that The preparation method of the La2O3-ZrO2 composite is as follows: ZrOCl2·8H2O and La(NO3)3·6H2O were dissolved in deionized water, and then 30 mL of anhydrous ethanol was added; Ultrasonication for 1 h, then adjusting the pH with NH4OH, followed by vigorous stirring for 30 min; Transfer to a high pressure reactor and react at 200°C for 20h; Then it was cooled naturally to room temperature and then centrifuged to obtain a precipitate, which was washed with deionized water and then dried at 70 °C for 12 h and then calcined.
6. The high refractive index large particle size glass microspheres for road marking according to claim 5, characterized in that: The molar ratio of ZrOCl2·8H2O and La(NO3)3·6H2O is 4.5:
1.
7. The high refractive index large particle size glass microspheres for road marking according to claim 6, characterized in that: The pH was adjusted to 10 with NH4OH.
8. The high refractive index and large particle size glass microspheres for road marking according to claim 7, characterized in that: The calcination condition is calcination at 900°C for 12h.
9. The method for preparing the high refractive index and large diameter glass microspheres for road marking according to claim 1, characterized in that: The method comprises the following steps: uniformly mixing titanium dioxide, silicon dioxide, barium nitrate, zirconium nitrate, zinc oxide, boric acid, calcium fluoride, Nb2O5 and La2O3-ZrO2, then melting them at 1200°C, quenching the molten product with water, drying it, ball milling it, and sieving it to obtain a 50μm precursor. The precursor is divided into two paths, and the precursor in each path is mixed with fuel gas and oxidant under the impetus of compressed air, and is sprayed into the combustion chamber through a nozzle; The heating temperature in the combustion chamber is set to 1300°C, and the jet velocity of the nozzle is 75 m / s; the jet trajectories of the two nozzles intersect at one point; The two jet paths share an intersection point, so that the molten glass bead precursor converges at this point; high refractive index glass microbeads are obtained through the screening process.
10. The spheroidization molding preparation method according to claim 9, characterized in that: The spray trajectories of the two nozzles intersect at an angle of 75° at one point.
Citation Information
Patent Citations
Pavement marking, reflective elements, and methods of making microspheres
CN101304954A
Rare earth aluminate single-phase or complex-phase nanocrystalline transparent ceramic material and preparation method thereof
CN101935208A
Preparation method of high-refractive-index glass beads
CN110818271A
Silicon borate and borosilicate glasses with high refractive index and low density
CN116529215A
Glass, glass blank for press-forming, optical element blank, and optical element
JP2018065747A
Cited By
Core-shell structure reflective microbead for road marking coating and preparation method of core-shell structure reflective microbead
CN121427355A
High-refractive-index glass bead and preparation method thereof
CN121698573A
High refractive index glass microbeads and method for making same
CN121698573B